Nitramino-polymer with ether bridges and 1,2,3-triazole subunits incorporated into the polymer chain - Pavel S. Gribov; Natalia N. Il'icheva; Natalia N. Kondakova; Evgenia R. Stepanova; Anatoly P. Denisyuk; Vladimir A. Sizov; Varvara D. Dotsenko; Valery P. Sinditskii; Aleksei B. Sheremetev (FirePhysChem, 2025)
The creation of novel energetic polymers for future advanced solid composite propellants and gunpowder is an urgent area of modern research. A simple and effective waste-free cycloaddition reaction between dialkyne and diazide comonomers, both bearing nitramine groups, for the synthesis of an energetic polymer containing explosophoric units in the polymer chain has been described. Neither solvent nor catalyst is required for the production of this polymer, the comonomers used are readily available, and the product does not need any purification, and, importantly, this protocol scales well. The resulting polymer, C1Z1, (C14H22N12O8)n, was comprehensively characterized by spectral and physico-chemical methods. Compatibility with energetic plasticizers (NG, DNDEG, DANPE), thermochemical characteristics and combustion features indicate the prospects of target polymer C1Z1 (density, ρ = 1.484 g/cm3; onset temperatures is 230 °C; positive enthalpy of the formation, ΔHf0 = +636 kJ/kg; burning rate at 10 MPa is 9.5 mm/s) as a binder base for energetic materials. Comparison of C1Z1 with nitrocellulose (NC) and their compositions with plasticizers revealed the advantages of C1Z1.